Curcumin mediates autophagy and apoptosis in granulosa cells: a study of integrated network pharmacology and molecular docking to elucidate toxicological mechanisms. (2nd November 2022) - Lin, Zhen; Liu, Huazhong; Yang, Chunyan; Zheng, Haiying; Zhang, Yu; Su, Weiming; Shang, Jianghua
Abstract: Curcumin (Cur) is a flavonoid derived from Curcuma longa L. that has been shown to have a variety of biological activities, but some previous studies have described its non-negligible negative effects on female reproduction and embryo development. To further explore the toxic stress effect, this study investigated apoptosis and autophagy of healthy buffalo ( Bubalus bubalis ) derived granulosa cells (GCs) exposed to Cur and/or autophagy inhibitors. Results showed that Cur declined viability of GCs in a concentration-dependent manner. Apoptosis was observed in Cur-treated GCs from 3 h. Meanwhile, under Cur stress, autophagosomes accumulated in cells, and the expression levels of autophagy key proteins LC3 and Beclin 1 were up-regulated, suggesting that Cur could induce autophagy in GCs. Early autophagy inhibitor 3-methyladenine (3-MA) increased the apoptosis rate of Cur exposed GCs, but the autophagosome degradation inhibitor chloroquine (CQ) had no effect on the apoptosis rate. The network pharmacological and molecular docking analysis indicated that the perturbation of IKK/NF-κB might be the cause of Cur toxicity toward GCs. This study unveiled another side of Cur pharmacological effects that programmed cell death can be induced by Cur in GCs, suggesting that it should be prudent to use Cur as a clinical drug for its side effects on the female reproductive system.